2017
DOI: 10.1002/slct.201700974
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Metal‐Free Visible Light Driven Photocatalyst: Graphene Oxide/Polythiophene Composite

Abstract: Graphene oxide/polythiophene (GO/PTh) composites were synthesized by in-situ polymerization of thiophene (Th) monomers on GO surfaces. Remarkable performance of GO/PTh composites for methylene blue (MB) photo-degradation under visible light has been achieved by tuning GO/Th ratio and graphene oxidation degrees. 100 % MB degradation was achieved by the composite within 30 min under visible light, its catalytic activity (0.1149 min À1 ) is 382 and 41 times higher than that of PTh (0.0003 min À1 ) and GO (0.0028 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The band gap of the GO and GO–poly(AMPS– co –AM) were estimated of 5.9 and 4.7 eV, respectively, by extrapolation of the corresponding curves. Clearly, the synthesized GO–poly(AMPS– co –AM) with a narrow band gap (toward GO) can be better semiconductor than the pristine GO and may have an application in optical fields and/or can be also used as a photocatalyst for degradation of different organic dye polluters …”
Section: Resultsmentioning
confidence: 99%
“…The band gap of the GO and GO–poly(AMPS– co –AM) were estimated of 5.9 and 4.7 eV, respectively, by extrapolation of the corresponding curves. Clearly, the synthesized GO–poly(AMPS– co –AM) with a narrow band gap (toward GO) can be better semiconductor than the pristine GO and may have an application in optical fields and/or can be also used as a photocatalyst for degradation of different organic dye polluters …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the performance of polythiophene incorporated in catalyst is also evaluated in the study done recently by Yu et al with graphene oxide [ 69 ]. It is observed that complete photodegradation of methylene blue (MB) model pollutants is reached after 30 min of visible light irradiation, as the catalytic activity of graphene oxide/polythiophene (GO/PTh) is enhanced by 382 and 41 times than that of pristine PTh and GO, respectively.…”
Section: Polythiophene Based Photocatalystmentioning
confidence: 99%
“…Since the properties of nanofibers can be changed by device parameters such as the applied voltage, the distance of the needle to the collector, the rotation speed of the collector, the injection speed and the polymer concentration, it is widely used to obtain nanofibers. [3,4] In this study, polythiophene (PTh), [5][6][7] one of the most used members of conductive polymers, [8,9] which is resistant to environmental conditions and has a stable chemical structure, was synthesized by chemical oxidation. Then, PTh/PSDA composites were obtained by synthesizing poly(sulfonic acid diphenyl aniline) (PSDA), [10] which is the sulfonated form of polyaniline on PTh.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, polythiophene (PTh), [5–7] one of the most used members of conductive polymers, [8,9] which is resistant to environmental conditions and has a stable chemical structure, was synthesized by chemical oxidation. Then, PTh/PSDA composites were obtained by synthesizing poly(sulfonic acid diphenyl aniline) (PSDA), [10] which is the sulfonated form of polyaniline on PTh.…”
Section: Introductionmentioning
confidence: 99%